2006
DOI: 10.1002/ejsp.339
|View full text |Cite
|
Sign up to set email alerts
|

The impact of perceived experience on likelihood judgments for self and others: an experimental approach

Abstract: This study examines the effect of an experimental manipulation of perceived experience on self and others' likelihood ratings for a set of relatively commonplace misfortunes. Participants were randomly assigned to a condition in which they were asked whether they had ever experienced the events (designed to induce higher perceived experience) or whether they had done so frequently, typically, etc. (designed to induce lower perceived experience). The manipulation led to increases in ratings of both perceived se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…It was suggested that when a negative mood is induced, other negative thoughts are activated and the judgements about the future are biased in a mood-congruent direction (Bower, 1981). Contrary, other studies revealed that the adults, after imagining themselves in different negative scenarios, showed a decrease in judgements of future negative events for both themselves and others, compared to the control condition (e.g., Harris, 2007;Rafaely et al, 2011) or compared to neutral or positive conditions (e.g., Chou, Lee, & Ho, 2007;Fedorikhin & Cole, 2004). To explain these findings it was suggested that negative moods may prompt more positive self-relevant thoughts and, consequently, mood incongruent response patterns may occur.…”
Section: Affective Statesmentioning
confidence: 97%
See 3 more Smart Citations
“…It was suggested that when a negative mood is induced, other negative thoughts are activated and the judgements about the future are biased in a mood-congruent direction (Bower, 1981). Contrary, other studies revealed that the adults, after imagining themselves in different negative scenarios, showed a decrease in judgements of future negative events for both themselves and others, compared to the control condition (e.g., Harris, 2007;Rafaely et al, 2011) or compared to neutral or positive conditions (e.g., Chou, Lee, & Ho, 2007;Fedorikhin & Cole, 2004). To explain these findings it was suggested that negative moods may prompt more positive self-relevant thoughts and, consequently, mood incongruent response patterns may occur.…”
Section: Affective Statesmentioning
confidence: 97%
“…Studies investigated the impact of experimentally induced negative affective states compared to a control condition on judgements of future events and used the imagination technique for various negative events (e.g., drinking problems, malfunction of the nervous system or agerelated diseases; Harris, 2007;Rafaely et al, 2011;Sparks et al, 2003). Mixed findings were reported on adult samples.…”
Section: Affective Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…Biased memories are an even more potent source of non-motivational self-enhancement and self-protection. When people work on collaborative tasks, for example, their own inputs are naturally more salient (Harris, 2007). Thus, it is important to distinguish between self-enhancement and self-protection as processes that are motivated by the desire to promote or protect a selfimage, and between self-enhancement and self-protection that are achieved as offshoots of non-motivated processes (Gramzow & Willard, 2006).…”
Section: What Kind Of Explanations Do Self-enhancement/self-protectiomentioning
confidence: 99%